La función sexual y su variación respecto a condiciones sociodemográficas en mujeres con vida sexual activa del departamento del Quindío (2021)
Female sexual functions are a component of sexuality that has been unknown to many women due to cultural and educational factors, which has repercussions on sexual health. The main objective of this research was to describe sexual function according to the sociodemographic conditions of women with an active sexual life in the department of Quindío. The work was developed with a descriptive quantitative methodology, with a sample of 51 women aged 20 to 60 years, who responded to the instrument of sociodemographic conditions and Blumel's Female Sexual Function Index (FSFI), which contains six dimensions: desire, arousal, lubrication, orgasm, satisfaction and pain. The results obtained indicated that most of the women in the sample were single, employed, with a sexual function of pain with the highest arithmetic mean, followed by satisfaction, lubrication, orgasm, arousal and to a lesser extent, desire. It was concluded that sexual function is higher when one is younger, with a high academic level, an stable partner, is independent and a non-Catholic religion